Health Professionals of Emergency Service: Evaluation of Triage and Ethical Values in Disaster Medicine - Şükran Sevimli; Recep Dursun; Sevdegül Karadaş (Eurasian Journal of Emergency Medicine, 2015)

(untitled)
Aim: To understand opinions of health professionals who work in emergency services about the application of basic concepts, such as triage, ethics, legal rules, to popularize problems they experience while they are providing health services after natural disasters, and to develop suggestions.Materials and Methods: In order to evaluate health service problems, a questionnaire tool was formulated regarding triage and ethics applications. The questionnaire was given to 133 emergency service workers with and without earthquake experiences. Data were analyzed using descriptive statistics with statistical significance set at p<0.001. The frequency distributions were taken into account and chi square test was performed to understand the differences between employees who had experienced earthquakes and those who had not.Results: In the survey, 57.7% of participants were male and 42.3% were female. The mean age of the participants’ was 29.8 years; 16.8% of them worked in the university hospital, 77.4% in the state hospital, and 5.8% in private hospitals. Of the participants, 51.1% were doctors, 43.1% were nurses, and 5.8% were emergency medical technicians; 48.2% of participants had experienced an earthquake and 52.6% had not. In addition, 27% of the participants had to consult regarding triage; 37.2% on triage and legal rules; 31.4% on triage, laws, and ethics; and 4.4% on triage and ethical principles.Conclusion:The results show that triage and legal regulations play an essential role in resource allocation and medical service presentation, while ethical principles are less considered in medical services after natural disasters. Inclusion of ethical training in natural disaster medicine education and its enhancement through regular rehearsals are essential.